2017
DOI: 10.7595/management.fon.2017.0010
|View full text |Cite
|
Sign up to set email alerts
|

Competence requirements for logistics managers in the Republic of Serbia

Abstract: This paper examines the competences that the employers in the logistics and supply chain management (SCM) field require most from employees in the Republic of Serbia. To reveal these competences, we conducted the study of online advertisements of logistics and SCM jobs published in the renowned national job portal Infostud. We used a deductive content analysis and related quantitative indicators to process and analyse the data. The results, among other conclusions, indicate the most required professional and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Other researchers have also investigated the presence of sustainability competences in addition to the commonly expected competences in job advertisements in supply chain management-related professions. Their results showed that sustainability skills were perceived as an important but less possessed skill among business analysts [25], interpersonal skills are more important while reverse and green logistics are less important skills to fulfill a logistics manager position [29] and skilled functional managers have a greater influence on sustainable management than general managers in terms of finding a balance between economic, social and environmental aspects [27]. Although our findings are similar to them, using the competency framework we developed allowed us to obtain a more detailed picture of the requirements for sustainability-related competencies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other researchers have also investigated the presence of sustainability competences in addition to the commonly expected competences in job advertisements in supply chain management-related professions. Their results showed that sustainability skills were perceived as an important but less possessed skill among business analysts [25], interpersonal skills are more important while reverse and green logistics are less important skills to fulfill a logistics manager position [29] and skilled functional managers have a greater influence on sustainable management than general managers in terms of finding a balance between economic, social and environmental aspects [27]. Although our findings are similar to them, using the competency framework we developed allowed us to obtain a more detailed picture of the requirements for sustainability-related competencies.…”
Section: Discussionmentioning
confidence: 99%
“…The usability of this data set in policy-data analysis was investigated by Cammeraat and Squicciarini in the OECD report [24]. Researchers thinking on a smaller scale are concerned with regional and temporal changes in the competence needs associated with particular occupations (e.g., business analyst [25], data scientist [26], functional controller [27], Corporate Social responsibility professional [28], logistic manager [29]), or changes in the structure of the labor market influenced by external factors (e.g., closures due to the COVID-19 pandemic [30]).…”
Section: Related Work In Analyzing Competence Needsmentioning
confidence: 99%
“…(2021) revealed that managers of seven large-scale companies recommend general management skills as the most important logistics skills, followed by IT skill as second and marketing skills as third. Cvetić et al. (2017) disclosed performance management is the most important indicator, followed by demand forecasting and inventory management.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Consequently, researchers have identified the most required professional and fundamental logistics competences to provide general recommendations for improvement in the relevant field. Cvetić et al. (2017) concludes that performance management and demand forecasting as amongst the most required professional competencies of a logistics and supply chain management.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies in the peer-reviewed literature have been carried out to examine the requirements cited in online job postings in the field of supply chain management. However, these studies have thus far been geographically limited to the USA (Radovilsky & Hegde, 2012;Radovilsky, Hegde, & Kandasamy, 2007;Rossetti & Dooley, 2010;Sodhi, Son, & Tang, 2008), Anglophone (Canada, UK, and USA), and Asian countries (China, India, Malaysia, and Singapore) (Shou & Wang, 2015), although a single country study has been conducted in Europe (Serbia) (Cvetić, Vasiljević, & Danilović, 2017).…”
Section: Introduction -The Assumption Of a Standard Profile For A Universal Purchasermentioning
confidence: 99%